Career development and systems theory : a new relationship - Patton, Wendy; McMahon, Mary. (Pacific Grove, Calif. : Brooks,Cole Publ., 1999)
Framework for career theory convergence using a metatheoretical approach.
Includes bibliographical references and index.
Keywords: Career development; Vocational guidance